Determinants of gestational syphilis among women attending prenatal care programs in the Brazilian Amazon - Uchôa, Thais Lopes do Amaral; Araújo, Eliete da Cunha; da Silva, Richardson Augusto Rosendo; Valois, Rubenilson; Azevedo Junior, Wanderson Santiago de; Nascimento, Valéria Gabriele Caldas; Aben-Athar, Cintia Yolette Urbano Pauxis; Parente, Andressa Tavares; Botelho, Eliã Pinheiro; Ferreira, Glenda Roberta Oliveira Naiff (Frontiers in Public Health, 2022)
Background There was a high proportion of pregnant women who were attending prenatal care who were not tested for syphilis or tested but not treated, among priority countries. The coverage for prenatal care visits, syphilis screening, and treatment are priority indicators for monitoring of the elimination of syphilis. The aim was to determine the factors associated with gestational syphilis among postpartum women who were in a prenatal care program in the Brazilian Amazon. Methods An unmatched case–control study was conducted at the hospital in Brazil. Data collection was carried out from November 2020 to July 2021 during hospitalization using a pretested structured questionnaire. The criteria for selection of cases and control followed the guidelines established by the Ministry of Health of Brazil; postpartum women with a laboratory diagnosis based on treponemal and/or nontreponemal tests, symptoms of syphilis or asymptomatic, treatment or not treated, and in a prenatal care program. Gestational syphilis cases were identified as women who tested positive for syphilis, and those who tested negative were controls, at minimally one prenatal care visit, childbirth, and/or the puerperium. The sample size encompassed 59 cases and 118 controls (1: 2 ratio of cases to controls). Data were analyzed using Minitab 20® and BioEstat 5.3® software. The odds ratio was calculated by multiple logistic regression. Results One hundred and seventy-seven postpartum women were included in the study, 59 cases and 118 controls. Among all participants, 95.5% (169) were tested for syphilis in any trimester during pregnancy and at the delivery and 4.5% (8) were tested in the maternity only, at the time childbirth and/or puerperium. The final multiple logistic regression model evidenced that cases had higher odds compared to controls if they had past history of sexually transmitted infections (AOR: 55.4; p: 0.00), difficulty talking about condom use with their sexual partner (AOR: 4.92; p: 0.01), one to six prenatal care visits (AOR: 4.93; p: 0.01), had not received a sexually transmitted infections test result in the maternity hospital (AOR: 4.09; p: 0.04), lower monthly income (AOR: 4.32; p: 0.04), or one to three miscarriages (AOR: 4.34; p: 0.01). Conclusion The sociodemographic, programmatic, obstetric, and sexual factors are associated with gestational syphilis among postpartum women.